Exosomes in schizophrenia: Pathophysiological mechanisms, biomarkers, and therapeutic targets - Yu Wang; Nousayhah Amdanee; Xiangrong Zhang (European Psychiatry, 2022)
While schizophrenia (SCZ) is a devastating psychiatric disorder that detrimentally affects a significant portion of the worldwide population, its diagnosis is traditionally based on a relatively subjective assessment of current symptoms and medical history, devoid of an objective diagnostic modality. Antipsychotic medications are commonly used in the treatment of SCZ; however, some patients have low remission rates or forsake treatment due to the associated multiple side effects, resulting in recurrent episodes of the disease and poor prognosis. These situations imply that the diagnosis, treatment, and prognosis of SCZ need to be improved to increase the odds of a better outcome. Mounting studies have found that extracellular vesicles (EVs) play essential roles in the central nervous system. They are implicated in several mechanisms closely associated with SCZ such as cellular communication and synaptic plasticity. They can additionally exhibit neuroprotective and therapeutic effects. Since they possess distinct constituents, are readily available, easily detectable, and dependent on the internal environment, they can potentially serve as reliable biomarkers for disease diagnosis. Moreover, their biological configuration along with their ability to increase the bioavailability of their constituents and modulate intricate intracellular reactions in target cells, propel EVs as new targets for treatment. This review paper summarizes relevant research pertaining to the roles of EVs in SCZ, with the aim of improving insights into SCZ pathogenesis and evaluating EVs as potential biomarkers in the diagnosis and treatment of SCZ.